Measuring gender sensitive climate adaptation in agrifood systems for climate finance - Eissler, Sarah; Magalhaes, Marilia; Ringler, Claudia; Bryan, Elizabeth (International Food Policy Research Institute, 2025)
There is a need for clear and flexible national-level frameworks to help countries identify their progress towards gender integration in climate adaptation. Gender-sensitive frameworks would also help strengthen gender considerations when determining climate financing and steer potential financing to accelerate progress towards gender equality. Without such frameworks, it becomes difficult to direct climate finance strategically to women in the AFS and to systematically track the adaptation outcomes associated with the funds they receive. This brief draws on a literature review of existing policies and frameworks and key informant interviews (KIIs) with experts in designing gender-informed national-level frameworks conducted by researchers at the International Food Policy Research Institute (IFPRI) under the Gender, Climate Change, and Nutrition (GCAN) Integration Initiative and the CGIAR Climate Action Science Program. In this brief, we summarize the need for clear and applicable national-level frameworks to measure gender integration in climate change adaptation strategies and how such guidance could be used to direct climate financing to address gender equality.